Prognostic role of visceral fat for overall survival in metastatic colorectal cancer: A pilot study. Issue 1 (January 2021) - Basile, Debora; Bartoletti, Michele; Polano, Maurizio; Bortot, Lucia; Gerratana, Lorenzo; Di Nardo, Paola; Borghi, Matteo; Fanotto, Valentina; Pelizzari, Giacomo; Lisanti, Camilla; Garutti, Mattia; Buriolla, Silvia; et al.
Summary: Background: Body composition, has been established as a risk factor for colorectal cancer diagnosis and disease progression. Aim of this study was to investigate the prognostic role of adiposity, especially visceral fat (VAT), in patients (pts) with metastatic colorectal cancer (MCRC). Material and methods: A retrospective cohort of 71 MCRC pts treated between 2013 and 2017 was evaluated. VAT was measured as cross-sectional (cm 2 ) area at the L3 level divided by the square of the height (m 2 ). A ROC analysis was performed to define a prognostic threshold according to VAT. Results: Before first-line therapy start, 40 pts (56%) had a body mass index (BMI) > 25 kg/m 2 . The obtained cut-off value for VAT was 44. Median OS was 30.97 months. At univariate analysis, primary tumor resection (HR 0.40, p = 0.029), VAT>44 (HR 2.85, p = 0.011) and metastasectomy (HR 0.22, p = 0.005) were significantly associated with OS. By multivariate analysis, VAT>44 (HR 2.6 ; p = 0.020) and metastasectomy were still significantly associated with OS. Conclusion: This exploratory study suggests a prognostic role for VAT in MCRC pts, with higher VAT values predicting worse outcome. Highlights: Visceral adipose tissue is involved in cancer development, growth and progression. The onset of colorectal cancer has been linked to excess adiposity. No standardized methods are available to measure visceral adiposity in cancer patients. A CT-derived index of visceral adiposity is capable to stratify prognosis in patients with metastatic colorectal cancer.